Factor influencing consumers’ willingness to pay for branded desserts - Siti Nur Atifah Mohd Jamil (2018)
Branded dessert nowadays has high demand from consumer especially in Klang Valley area, however this will lead to impact for the local and traditional dessert producer. By using the marketing mix strategy this will helping the local producer to compete with the branded dessert branch. The 7P’s (product, place, promotion, price, physical evidence, people and process) elements in marketing mix are used to support the business. Past studies have proven that using marketing mix gave high impact towards company business in marketing the product. Furthermore, this study tends to investigate the factors influencing the consumers’ willingness to pay (WTP) for the branded dessert. To obtain a more reliable result, a quantitative research is carried out to investigate the topic. A total of 400 questionnaires were distributed in the Klang Valley area and the results were analyzed using SPSS (Descriptive, Chi-square, Factor Analysis and Multiple Regression). Finding showed that experience, taste & packaging and culture & tradition have positive relationship toward consumer’s willingness to pay towards branded dessert. The overall results for consumer’s willingness to pay for branded dessert show a good experience infer the consumer’s willingness to pay for branded dessert. However, to get a better understanding, further study can be done that covers the other district and enlarge sample size.